Use of Green Inhibitors for Concrete Armor Protection Against H2SO4 Corrosion - Lame (Galo), A.; Kokalari (Teli), E.; Jano, A. (Asian Journal of Chemistry, 2013)
The aim of this study to use the green inhibitors, friendly with environment and investigation of their efficiency in corrosion protection. As green inhibitor, is used one kind of polysaccharide (galactomannan), extracted from the endosperms of some leguminosae plants as coffee beans and chickpeas. Corrosion efficiency of these extracts in sulfuric acid media in presence of chloride ions (blank) was tested for low alloy carbon steels marked as: Steel 39, Steel 44 and iron B-500 (applied to concrete as reinforcing bars). The concentrations of aggressive species are: 1 mol/L H2SO4 + 10-3 mol/L Cl– (in form of NaCl). The efficiency of these extracts, at certain concentration (0.75 g/L), against blank, initially was investigated by mass loss measurements. The results compared with protection efficiency of (I–) ions, which are added in blank as KI with 0.01 mol/L. The electrochemical techniques as potentiodynamic polarization, accompanied with work surface microscope study, are used for optimization of inhibitor concentration. The inhibition action of galactomannan was discussed in terms of its horizontal adsorption.